Evidence-Based Social Sciences and Practices: A Scoping Review - Lilia Raitskaya; Elena Tikhonova (National Research University Higher School of Economics, 2024)
Introduction: The evidence-based medicine (EBM) was introduced in the 1990s, paving the way for the new approaches to science methodology and research evidence that changed medicine-related practices. Following the EBM, social sciences ranging from education to public governance and policymaking entered a new stage of knowledge production and dissemination. Each evidence-based social science field produces its own evidence and evidence synthesis laying the foundation for efficient social practices. Pilot searches failed to bring complex and complete evidence-based methodology for social sciences. Purpose: This scoping review aims to identify the scope of the evidence-based social sciences and practices as an emerging field. Method: The review adhered to the PRISMA extension for scoping reviews, and the PPC framework. The eligibility criteria include problem (population), concept, context, language, time period, types of sources, geographical location, databases, areas of research. The searches to identify relevant publications entail searches in the Scopus database. The studies were identified and selected by screening titles, abstracts and full texts, totalling 35 documents. Results: The results cover search and selection outcomes; a bibliometric analysis, the breakdown of the publications among the four thematic clusters; the findings relating to evidence-based medicine and practice methodology applicable to social sciences; the analysis of the research area of evidence-based social sciences and practices; the social science practices by sectors. Much of the EBM methodology was directly borrowed by social sciences. Though, the major controversy was found in the hierarchy and levels of evidence as social sciences are subject to human choices. Randomized controlled trials and systematic reviews were analysed in the context of social sciences. The most elaborated and fast developing evidence-based areas in social sciences contained evidence-based education and evidence-based policymaking, with systems of governmental agencies and institutions introducing these evidence-based practices. Сonclusion. The review attained the objective and gave answers to the research questions. Only few studies were published to comprehensively address the emerging field of evidence-based social sciences and practices. Fragmentated sub-fields are covered unevenly, with many mythological divergences and disputed issues, including the quality of evidence, their weight and hierarchy, types of research.